Screening for depleted uranium in the United Kingdom armed forces: who wants it and why?. Issue 7 (11th June 2004) - Greenberg, Neil; Iversen, Amy C; Unwin, Catherin; Hull, L; Wessely, S
Abstract : Background: Depleted uranium (DU) use has been implicated in the poor health of many service personnel who have served in the Gulf and the Balkans. Although the health related risks are thought to be small the UK government has offered to set up a voluntary screening programme for service personnel. This study aimed to find out the characteristics and possible exposures to DU for those personnel who desire DU screening. Methods: This study looks at 2369 UK service personnel who were asked if they wanted to be screened for DU. Subjects were asked about their perceived exposure to deployment associated risks including DU and a number of psychological health measures. Results: The study found that 24% of the cohort wanted screening, a figure that if extrapolated to all those who have been offered screening would represent 36 720 requests for screening. Those who wanted DU screening were younger, of lower rank, and more likely to be from the Royal Navy or Army rather than the Royal Air Force. Those requesting DU screening reported poorer health both subjectively and as measured by the GHQ-12 and a symptom checklist. They also reported more exposure to DU and to other deployment associated risks while in military service. Using combat exposure as a proxy for a significant risk of having been exposed to DU, there was a significant correlation. Conclusions: This study found that the desire for DU screening is more closely linked to current health status rather than plausible exposure to DU.